(3GdQCi hGdeThQIs - (3GdMcje CHh GdMSf Ydj Hf CMeO GdeJWHHs
(3ChdgG (B:s
(3GdMeO ddg GdPi CHOY HMceJg eG Od Ydi cfg eYQaJg hGdEbQGQ HQHhHjJg s
(3BNQgG (B:s
(3bO cGf SHjdc Cf JSJTjQfi ai gPG GdQCi HGdQCi ef bHd Cf JMjW Hc YSGcQ GdefUhQ, aCQSdJ eKdkG hGddg CYde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdTjN YHOGdYRjRGdMHTi GdNGUg HeOjfg BH s
Keywords: (3GdeYGQa GdYGeIs